KNOWLEDGE, AWARENESS AND PREVALENCE OF NOSOCOMEPHOBIA AMONG UNDERGRADUATE DENTAL STUDENTS - A QUESTIONNAIRE SURVEY - Sadhana Karunakaran, Dhanraj Ganapathy, L. Keerthi Sasanka, (Drugs and Cell Therapies in Hematology, 2022)
Introduction: Phobia is a form of anxiety disorder in which a person experiences irrational fear about a situation, place or object. Nosocomephobia is fear of hospitals. It is also known as “medical phobia”. Symptoms of nosocomephobia include increased heart rate, obsessive worrying, excessive sweating , nauseated feeling etc. Treatment for this phobia includes listening to doctors advice, having faith in doctors and medicines and cooperating with doctors and nurses. Aim: To assess prevalence and perception about nosocomephobia among dental students. Materials and methods: This survey was done online using google forms. This study involved students (17-25 years) of saveetha dental college and hospital. The number of students participated in this study was 100. The number of questions asked in the survey was 10. Statistical analysis was done using spss software version 23. Descriptive analysis was done and pie charts were formed.Chi square test was done and bar charts were generated. Results: From the present study, out of 100 dental students affected by nosocomephobia, 49% of students had fear of injections (36 females and 13males), 20% of the students had fear of knife/tweezers (10 males and females), 20% of the students get disturbed with the phenolic odour of the hospital (16 females and 4 males), 11% of the students get disturbed with the taste of the tablets/tonics (9 females and 25 males ) . 59% of the students have no idea about resolving their phobia (19 males and 40 females), 41% of the students are determined to resolve their phobia (10 males and 31 females) Conclusion: Nosocomephobia is more prevalent among females than males. Females are more determined to take initiatives to overcome this phobia. More awareness should be created among medical/dental students regarding nosocomephobia and the necessity to take initiatives to overcome this phobia.